Proceedings of the Ninth International Conference on Applied Linguistics (CONAPLIN 9) 2017
DOI: 10.2991/conaplin-16.2017.68
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Grammar through Data-Driven Learning (DDL) Approach

Abstract: Abstract-Although English has been taught as a compulsory subject from elementary to college level, many students consider English a challenging one especially when dealing with grammar. This paper reported an implementation of teaching grammar to students specialized in midwifery by integrating a Data-Driven Approach (DDL) into grammar teaching. DDL approach has gained popularity in English Language Teaching (ELT) in the last decade considering its benefits to empowering students to learn grammar inductively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
3
4
0
Order By: Relevance
“…With regard to the second research question, the results from the questionnaire show that some of the students reflect positive attitudes towards DDL activities as they found it fun and not boring (Boontam & Phoocharoensil, 2018). The results from the survey were found to be similar with a previous study of Yepes and Krishnamurthy (2010) that most of the learners considered DDL as a helpful method for acquiring new grammatical knowledge and wished to learn other English lessons through DDL activities (Lin & Lee, 2015;Nugraha et al, 2017). Interestingly, in this current study, DDL could help students retain their long-term memory knowledge and guide them to be active learners in the classroom since they reflected DDL differed from traditional classroom (Lin & Lee, 2015;Nugraha et al, 2017;Boontam & Phoocharoensil, 2018).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…With regard to the second research question, the results from the questionnaire show that some of the students reflect positive attitudes towards DDL activities as they found it fun and not boring (Boontam & Phoocharoensil, 2018). The results from the survey were found to be similar with a previous study of Yepes and Krishnamurthy (2010) that most of the learners considered DDL as a helpful method for acquiring new grammatical knowledge and wished to learn other English lessons through DDL activities (Lin & Lee, 2015;Nugraha et al, 2017). Interestingly, in this current study, DDL could help students retain their long-term memory knowledge and guide them to be active learners in the classroom since they reflected DDL differed from traditional classroom (Lin & Lee, 2015;Nugraha et al, 2017;Boontam & Phoocharoensil, 2018).…”
Section: Discussionsupporting
confidence: 66%
“…Some scholars (such as Yepes & Krishnamurthy, 2010;Huang, 2014;Lin & Lee, 2015;Nugraha et al, 2017 andBoontam &Phoocharoensil, 2018) found the advantages of DDL in grammar teaching. To illustrate, the research by Yepes and Krishnamurthy (2010) explored the effectiveness of both corpus-based and corpus-driven approaches by employing the Aston Corpus Network (ACORN) to teach Spanish grammar.…”
Section: Previous Empirical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire and interview results show that the students have positive attitudes towards learning through a DDL method as they found it fun, interesting and challenging (Flowerdew 2012). Consequently, the majority of them wanted to study other English lessons through DDL in the future as they considered this method as a helpful resource for learning new grammatical knowledge, which is conforming to other related studies (Boulton 2010, Yepes & Krishnamurthy 2010, Nugraha, Miftakh & Wachyudi 2017. Moreover, it was found that DDL seems to help students retain their knowledge in the long term (Lin & Lee 2015, Smart 2014).…”
Section: Research Question Ii: What Are Young Thai Efl Learners'supporting
confidence: 62%
“…Bearing these changes in Russian engineering education in mind, there is a need to improve existing programs and develop new ones in order to upgrade the quality of engineering training (Almetov et al, 2020;Gerasimova et al, 2022;Kharlamova et al, 2023;Sveshnikova et al, 2022). It is worth mentioning that currently many foreign and Russian higher education systems are developing and applying educational standards and approaches to learning, including English, with due account for the widespread use of modern information technology that can influence the acquisition of the necessary knowledge and skills (Aleryani et al, 2019;Rus, 2019;Nikonova et al, 2023;Varlakova et al, 2023). Thus, the dynamically developing approaches to learning English based on the use of online technology and databases can also include the use of text corpora (Fauzan et al, 2022;McGrath et al, 2022;Nugraha et al, 2017).…”
Section: Introductionmentioning
confidence: 99%